Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/lsm.22826
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral Erbium:YAG laser for the management of urinary symptoms of genitourinary syndrome of menopause: A pilot study

Abstract: ObjectivesGenitourinary syndrome of menopause (GSM) combines the conditions of vulvovaginal atrophy (VVA) and urinary tract dysfunction, which is a result of urethral atrophy. There are several treatment methods available for the management of vulvovaginal symptoms of GSM, whereas urinary tract dysfunction often remains overlooked and undertreated. The objective of this pilot study was to assess the safety and efficacy of intraurethral Er:YAG laser treatment of urinary symptoms of GSM.Patients and MethodsPatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 25 publications
2
39
0
2
Order By: Relevance
“…23 Seven studies had improvement in GSM as a primary outcome, but also included women with SUI. 25,28,40,44,[50][51][52] These studies also reported a significant reduction in the ICIQ-UI SF scores that was sustained at the 1-year follow up (P < 0.01). 25,50,51 In the longer term, the effect was no longer present at the 2-year follow up, 52 but Gonz alez Isaza reported a positive effect up to 3 years after treatment (P < 0.001).…”
Section: Urinary Incontinencementioning
confidence: 69%
See 3 more Smart Citations
“…23 Seven studies had improvement in GSM as a primary outcome, but also included women with SUI. 25,28,40,44,[50][51][52] These studies also reported a significant reduction in the ICIQ-UI SF scores that was sustained at the 1-year follow up (P < 0.01). 25,50,51 In the longer term, the effect was no longer present at the 2-year follow up, 52 but Gonz alez Isaza reported a positive effect up to 3 years after treatment (P < 0.001).…”
Section: Urinary Incontinencementioning
confidence: 69%
“…25,28,40,44,[50][51][52] These studies also reported a significant reduction in the ICIQ-UI SF scores that was sustained at the 1-year follow up (P < 0.01). 25,50,51 In the longer term, the effect was no longer present at the 2-year follow up, 52 but Gonz alez Isaza reported a positive effect up to 3 years after treatment (P < 0.001). 28 There were three other GSM studies in which women with unspecified incontinence were included showing significant improvement on the ICIQ-UI SF scores at 4 weeks of follow up (P < 0.001) 42 and 12 months of follow up (P < 0.001), 53 as well as a satisfaction rate of 75%.…”
Section: Urinary Incontinencementioning
confidence: 69%
See 2 more Smart Citations
“…In human soft tissue, the 2940 nm erbium yttrium‐aluminum‐garnet medium (Er:YAG) laser in the non‐ablative thermal mode has been shown to stimulate deep collagen remodeling and improve tightness and elasticity of the treated area . This non‐ablative treatment modality has been evaluated in several studies . A study evaluating Er:YAG laser treatment compared with topical estrogen therapy for GSM‐related symptoms demonstrated greater improvement in symptoms (irritation, dyspareunia, dryness, chronic leukorrhea) of the laser‐treated group up to 18 months of follow‐up after treatment.…”
Section: Discussionmentioning
confidence: 99%